Direct Oral Anticoagulants for Pulmonary Embolism - Pizzi, Roberto; Cimini, Ludovica Anna; Ageno, Walter; Becattini, Cecilia (Hämostaseologie, 2024)
Venous thromboembolism (VTE) is the third most common cardiovascular disease. For most patients, the standard of treatment has long consisted on low-molecular-weight heparin followed by vitamin K antagonists, but a number of clinical trials and, subsequently, post-marketing studies have shown that direct oral anticoagulants (DOACs) with or without lead-in heparin therapy are effective alternatives with fewer adverse effects. This evidence has led to important changes in the guidelines on the treatment of VTE, including pulmonary embolism (PE), with the DOACs being now recommended as the first therapeutic choice. Additional research has contributed to identifying low-risk PE patients who can benefit from outpatient management or from early discharge from the emergency department with DOAC treatment. There is evidence to support the use of DOACs in intermediate-risk PE patients as well as in high-risk patients receiving thrombolytic treatment. The use of DOACs has also been proven to be safe and effective in special populations of PE patients, such as patients with renal impairment, liver impairment, and cancer.
Keywords: pulmonary embolism; treatment; direct oral anticoagulants